Indian Muslim minorities and the 1857 Rebellion : religion, rebels, and jihad - Morgenstein Fuerst, Ilyse R. (International library of colonial history, 2017)
"While jihad has been the subject of countless studies in the wake of recent terrorist attacks, scholarship on the topic has so far paid little attention to South Asian Islam and, more specifically, its place in South Asian history. Seeking to fill some gaps in the historiography, Ilyse R. Morgenstein Fuerst examines the effects of the 1857 Rebellion (long taught in Britain as the 'Indian Mutiny') on debates about the issue of jihad during the British Raj. Morgenstein Fuerst shows that the Rebellion had lasting, pronounced effects on the understanding by their Indian subjects (whether Muslim, Hindu or Sikh) of imperial rule by distant outsiders."--